Factors determining the quality of health services provided to COVID-19 patients from the perspective of healthcare providers: Based on the Donabedian model - Moayed, Malihe Sadat; Khalili, Robabe; Ebadi, Abbas; Parandeh, Akram (Frontiers in Public Health, 2022)
Objectives The present study aims to explain factors determining the quality of health services provided to COVID-19 patients from the perspective of healthcare providers based on the Donabedian model. Method This qualitative study was conducted at a referral hospital on COVID-19 patients in Tehran, in 2020. The data were collected through individual and semi-structured interviews from 20 participants using the purposive sampling method. Besides, data analysis was conducted simultaneously using the directed content analysis method. Results Data analysis results produced 850 primary codes in three predetermined categories of the Donabedian model, including the structure (organizational readiness and continuous training), the process (effective management and leadership, safe care, and comprehensive care measures) and outcomes (professional excellence, quantitative and qualitative improvements in hospital services, and acceptability of healthcare professionals). Conclusion The results of this study can help managers better understand how a public health crisis affects the structure of organizations providing care and treatment, quality of treatment processes in the organization, and the consequences. In addition, this study can be used as a model for optimizing the structures and processes to improve outcomes.